Happiness and its Relationship with Job Burnout in Nurses of Educational Hospitals in Tabriz, Iran - Tahere Javadi Sharif; Mina Hosseinzadeh; Nader Mahdavi; Hossein Namdar Areshtanab; Geoffrey L. Dickens (Shiraz University of Medical Sciences, 2020)
Background: Happiness is a positive feeling that is vital and significant to maintain health. Nurses are working in difficult conditions which may heavily affect their level of happiness and ability to provide care. Job burnout is a mental reaction against some persistent source of workplace stress. The purpose of this study was to identify happiness and its relationship with job burnout in nurses working at Tabriz's educational hospitals. Methods: This descriptive-correlational study was conducted on 344 nurses working at Tabriz's hospitals in 2018. The subjects were selected by means of proportionate stratified random sampling. Data were collected using three questionnaires (demographic information, job burnout with 22 items and three subscales and Oxford happiness with 29 items) and analyzed in SPSS version16 using descriptive statistics. Statistical tests such as Pearson correlation coefficient, independent t-test, one-way ANOVA, and multiple linear regression analysis were used to analyze the data. Results: The age range of the participants was 23-57 years with a mean of 35.9±7.5. The mean score of happiness was 64.2±11.5, (score range 35 to 116), which suggests an average level of happiness among the nurses. There was a negative correlation between happiness and total job burnout (r=-0.29, p <0.001). This negative correlation remained significant (B=-0.15, p <0.001) even when nurses' perception of own health status (B=-5.24, P=0.01), history of illness (B=-4.47, P=0.04), job position (B=-6.61, P=0.001), and type of employment (B=3.56, P=0.03) as potential confounding factors were adjusted. Conclusion: Considering the reverse relationship between job burnout and happiness, it is suggested that managers try to improve the workplace by managing condition which could lead to job burnout, and therefore use the results to increase the happiness of nurs.